ゼータ関数とイータ関数の関係

ゼータ関数とイータ関数は以下の関係がある。
\[ \eta(s)=(1-2^{1-s})\zeta(s) \]

\begin{align*} \eta(s) & =\sum_{k=1}^{^{\infty}}(-1)^{k+1}k^{-s}\\ & =\sum_{k=1}^{^{\infty}}(-1)^{2k+1}(2k)^{-s}+\sum_{k=1}^{^{\infty}}(-1)^{2k}(2k-1)^{-s}\\ & =-\sum_{k=1}^{^{\infty}}(2k)^{-s}+\sum_{k=1}^{^{\infty}}(2k-1)^{-s}\\ & =-\sum_{k=1}^{^{\infty}}(2k)^{-s}+\sum_{k=1}^{^{\infty}}k^{-s}-\sum_{k=1}^{^{\infty}}(2k)^{-s}\\ & =-2^{1-s}\sum_{k=1}^{^{\infty}}k^{-s}+\sum_{k=1}^{^{\infty}}k^{-s}\\ & =(1-2^{1-s})\zeta(s) \end{align*}

ページ情報

タイトル

ゼータ関数とイータ関数の関係

URL

https://www.nomuramath.com/wsvsj63f/

SNSボタン